Kodo poisoning and its management - Deepika, C; Hariprasanna, K (Indian Farming, 2023)
Kodo millet is a nutricereal, and staple food for many tribal and economically weaker sections in India. It is one of the hardiest crops, drought tolerant with high yield potential and excellent storage properties. But, its production and consumption are on the decline due to various factors. Kodo poisoning is one of the major factors impeding its consumption and this problem needs an immediate attention for effective management. The fear of kodo poisoning has emerged as a serious economic constraint for kodo millet cultivation, consumption and popularisation. This article would help in management of kodo poisoning thereby enabling its prevention, and enhancing the consumption and popularisation.